The Golden Blueprint: An Exploration of the Winning Qualities Shared Among Kiwi Olympic Greats - McCarthy, Joshua (Auckland University of Technology, 2025)
The research draws on visual storytelling, assemblage, media representations of Olympic athletes, and growth and winning mindsets. The research explores how five shared winning qualities of multiple Kiwi Olympians can form a blueprint to inspire young adults in New Zealand to pursue their own goals. A practice-led methodology within an artistic research paradigm guided the project, supporting an iterative, reflexive, and hands-on design process. The work unfolded in three phases: Research (establishing the conceptual foundation), Ideation (developing the core concepts), and Design (realising the final visual outcomes). The study shows how editorial design and assemblage can effectively communicate values-based messages to counter the negative effects of social media by presenting the stories of Kiwi Olympians, intertwined by shared qualities, to encourage the pursuit of sporting goals.
Keywords: Assemblage; New Zealand Olympians; Practice-led research; Visual narrative; Winning Mindset